A theoretical study on mitigation of CO2 through advanced deep eutectic solvents. (August 2015) - García, Gregorio; Atilhan, Mert; Aparicio, Santiago
Graphical abstract: Highlights: Theoretical analysis of the suitability of deep eutectic solvents for CO2 capture. Density functional theory simulations for nanoscopic characterization. Mechanism of CO2 capture by deep eutectic solvents. Water effect on deep eutectic solvent performance as CO2 sorbents. Abstract: A density functional theory study on the molecular level characterization of the mechanism of CO2 capture by deep eutectic solvents is reported here. To our knowledge, this is the first work aimed to the application of DFT simulations to investigate CO2 capture by DES at the molecular level. DFT studies on choline chloride based deep eutectic solvents involving glycerol and malonic acid as hydrogen bond donors were carried out. The analysis of the molecular geometries of selected DESs, as well as the characterization of the hydrogen network shed some light on the relationship between the molecular structure and the melting point. In addition, due to the high hygroscopic character of choline based deep eutectic solvents, water effect on CO2 capture was also analyzed. Our density functional theory simulations offer useful information in the suitability of DESs as CO2 capture agents. In short, selected deep eutectic solvents could provide high efficiencies for CO2 capture, for which water presence has not serious drawbacks.